2008
DOI: 10.2174/138161208786264089
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Polymorphisms of TLR4 and CD14 Genes and Alzheimers Disease

Abstract: Alzheimer's disease (AD) is a heterogeneous and progressive neurodegenerative disease which in Western society mainly accounts for clinical dementia. Inflammation plays a key role in AD and dissecting the genetics of inflammation may provide an answer to the possible treatment. Hence, the better understanding of different molecular and cellular inflammatory mechanisms is crucial for complete knowledge of AD pathophysiology, and for its prevention and drug therapy. Accordingly, in the present study we evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 46 publications
2
42
0
1
Order By: Relevance
“…We evidenced for the first time that TLR2 and TLR4 mRNAs were up-regulated and plasma levels of them were also higher in AD patients than in controls. Variants of TLR2 and TLR4 gene were thought to influence the susceptibility to AD [12][13][14][15]24,25]. Polymorphisms might affect the expression of the target gene and cytokine production of peripheral blood leukocytes by affecting the regulatory effect of the 3′ UTR of the TLR4 gene [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We evidenced for the first time that TLR2 and TLR4 mRNAs were up-regulated and plasma levels of them were also higher in AD patients than in controls. Variants of TLR2 and TLR4 gene were thought to influence the susceptibility to AD [12][13][14][15]24,25]. Polymorphisms might affect the expression of the target gene and cytokine production of peripheral blood leukocytes by affecting the regulatory effect of the 3′ UTR of the TLR4 gene [26].…”
Section: Discussionmentioning
confidence: 99%
“…For example, our previous two studies demonstrated that microsatellite polymorphisms of TLR2 can increase risk of LOAD [12] and TLR4/11367 polymorphism was associated with LOAD in a Han Chinese population [13]. Another two studies analyzed the association between AD and TLR4 +896A/G [14,15], that is a common adenine to guanine substitution in TLR4, causing the replacement of an aspartic acid residue by glycine at amino acid 299 (Asp299Gly). They indicated that patients with the Asp299 allele have an increased incidence of AD in an Italian population.…”
Section: Introductionmentioning
confidence: 99%
“…The D299G SNP is implicated in gastric cancer, athero-182 sclerosis, sepsis, and asthma, and a G11481C mutation has been linked to prostate cancer (El-Omar et al, 2008). A number of studies also suggest a possible role for TLR4 in cardiovascular disease (Frantz et al, 2007;Satoh et al, 2008), inflammatory bowel disease (Fukata and Abreu, 2007), Alzheimer's disease (Balistreri et al, 2008), rheumatoid arthritis (van den Berg et al, 2007), renal disease (Anders et al, 2004), obesity, and diabetes types I and II (Kim, 2006); whether the genetic evidence will support the disease tissue and model observations remains to be proven. In mouse models, for example, inhibition of TLR4 is beneficial in mouse models of rheumatoid arthritis (Eder et al, 2004), and patients with the disease carrying the D299G mutation have altered macrophage responses to LPS (Roelofs et al, 2008), but a clear genetic link between TLR4 and rheumatoid arthritis has yet to be found.…”
Section: Diseases Linked With Toll-like Receptormentioning
confidence: 99%
“…The microglia activation can be due to local or systemic inflammation. In fact a strong local inflammatory stimulus such as a previous head trauma is a risk factor for AD and several epidemiological studies clearly show that blood elevations of acute phase proteins, markers of systemic inflammatory stimuli, may be risk factors for cognitive decline and dementia [72][73][74].…”
Section: Brainmentioning
confidence: 99%